Antimycobacterial activity of intertidal sediment-derived bacteria from False Bay, South Africa - Thagulisi, Funanani; Baatjies, Lucinda; Sharma, Abhinav; Ngom, Justice Trésor; Nyambo, Kudakwashe; Jooste, Tracey; Tapfuma, Kudzanai Ian; Mavumengwana, Vuyo (Frontiers in Microbiology, 2026)
Tuberculosis (TB), caused by Mycobacterium tuberculosis, remains a global health burden due to the pathogen’s ability to develop resistance to current treatment options. Consequently, drug discovery studies are essential for identifying new antimycobacterial agents with novel mechanisms of action. This study investigated the antimycobacterial activity of crude extracts derived from mixed culturable bacteria isolated from intertidal marine sediments. The bacterial diversity of the bioactive mixed cultures was characterized using 16S rRNA gene-based metagenomic analysis. Their pathogen-targeted effects were evaluated against Mycobacterium smegmatis mc2155 and M. tuberculosis H37Rv, and THP-1-derived macrophages infected with M. smegmatis mc2155. Of the 48 mixed bacterial crude extracts derived from 17 intertidal marine sediments, five-PPB1, GCR1, BB1, PPB2, and CR1-demonstrated strong antimycobacterial activity against M. smegmatis mc2155 and M. tuberculosis H37Rv with minimum inhibitory concentrations ranging from 31.25 to 62.50 μg/mL and 7.8125 to 15.625 μg/mL, respectively. At 62.50 μg/mL, CR1 significantly reduced the intracellular M. smegmatis mc2155 burden in THP-1-derived macrophages, resulting in 28.08 ± 4.25% mean decrease in bacterial survival (p < 0.0001) and 94.4% ± 1.14 mean growth inhibition. From the CR1 mixed cultures, nine axenic bacterial isolates were cultivated, and their resulting crude extracts were evaluated for bioactivity. The identified isolates included Marinobacter maritimus, Psychrobacter celer, Pseudomonas benzenivor, Bacillus altitudinis, Bacillus aerius, Bacillus stratosphericus, and Paenibacillus glucanolyticus. Metabolite profiling of axenic crude extracts identified several compounds, including tenacibactin B, maremycin D1, and tubercidine. These findings suggest that South African intertidal marine sediments host diverse microbial communities capable of producing novel antimycobacterial agents.